2021
DOI: 10.1159/000516665
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-Like Growth Factor 1 in the Preterm Rabbit Pup: Characterization of Cerebrovascular Maturation following Administration of Recombinant Human Insulin-Like Growth Factor 1/Insulin-Like Growth Factor 1-Binding Protein 3

Abstract: Following preterm birth, serum levels of insulin-like growth factor 1 (IGF-1) decrease compared to corresponding in utero levels. A recent clinical trial indicated that supplementation with recombinant human (rh) IGF-1/rhIGF-binding protein 3 (rhIGF-1/rhIGFBP-3) prevents severe intraventricular hemorrhage (IVH) in extremely preterm infants. In a preterm rabbit pup model, we characterized endogenous serum and hepatic IGF-1, along with brain distribution of IGF-1 and IGF-1 receptor (IGF1R). We then evaluated the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
8
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…On the other hand, it cannot be excluded that the transient downregulation of TTR mRNA, encoding protein transthyretin, might negatively affect hippocampal IGF1R expression ( Vieira et al, 2015 ), as it is known to act synergistically with IGF-1 on IGF1R activation ( Vieira et al, 2016 ). Alternatively, the transient alterations in the expression of IGF-1 and related genes might arise before P5, as it was recently shown for IGF-1 expression in the choroid plexus of preterm rabbit pups treated with IGF-1/IGFBP3 complex ( Gram et al, 2021 ). In this study, the greatest changes in gene expression were observed at 24 h and limited changes at 72 h after treatment start, suggesting an acute and transient effects of systemic IGF-1 on brain gene expression ( Gram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…On the other hand, it cannot be excluded that the transient downregulation of TTR mRNA, encoding protein transthyretin, might negatively affect hippocampal IGF1R expression ( Vieira et al, 2015 ), as it is known to act synergistically with IGF-1 on IGF1R activation ( Vieira et al, 2016 ). Alternatively, the transient alterations in the expression of IGF-1 and related genes might arise before P5, as it was recently shown for IGF-1 expression in the choroid plexus of preterm rabbit pups treated with IGF-1/IGFBP3 complex ( Gram et al, 2021 ). In this study, the greatest changes in gene expression were observed at 24 h and limited changes at 72 h after treatment start, suggesting an acute and transient effects of systemic IGF-1 on brain gene expression ( Gram et al, 2021 ).…”
Section: Discussionmentioning
confidence: 91%
“…Alternatively, the transient alterations in the expression of IGF-1 and related genes might arise before P5, as it was recently shown for IGF-1 expression in the choroid plexus of preterm rabbit pups treated with IGF-1/IGFBP3 complex ( Gram et al, 2021 ). In this study, the greatest changes in gene expression were observed at 24 h and limited changes at 72 h after treatment start, suggesting an acute and transient effects of systemic IGF-1 on brain gene expression ( Gram et al, 2021 ). Our RNA-seq data of the entire hippocampal structure at P5 showed marginal changes in gene expression, while IHC results at the same time point indicated clear region-dependent differences between groups.…”
Section: Discussionmentioning
confidence: 91%
“…The mitogenic peptide insulin-like growth factor 1 (IGF) is involved in the regulation of cell metabolism and angiogenesis, and is an essential element in fetal brain development [ 1 , 2 ]. Serum levels of IGF-1 are considerably lower following preterm birth compared to the fetus of corresponding gestational age remaining in utero [ 3 5 ]. Reduced postnatal serum levels of IGF-1 are associated with elevated risk for neurodevelopment impairment, along with poor weight gain and lower brain volumes [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…The selective transcytosis of systemic IGF-1 through the ChP is believed to involve the IGF-1 receptor (IGF-1R) which is abundantly expressed in the ChP [ 9 ]. However, in the immature brain of the preterm rabbit pup, the IGF-1R has been shown to be mainly located at the epithelial border of the ChP, thereby facing the CSF, and to a lesser extent at the endothelial side [ 3 ]. Therefore, it is reasonable to consider other putative mechanism of IGF-1 transcytosis through the ChP besides the involvement of the IGF-1R, such as in extracellular vesicles encapsulation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation